2011
DOI: 10.1245/s10434-011-1624-4
|View full text |Cite
|
Sign up to set email alerts
|

Surgical Prevention of Arm Lymphedema After Breast Cancer Treatment

Abstract: LYMPHA represents a valid technique for primary prevention of secondary arm lymphedema with no risk of leaving undetected malignant disease in the axilla.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
124
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 152 publications
(126 citation statements)
references
References 15 publications
1
124
0
1
Order By: Relevance
“…37 Others have advocated for prophylactic lymphovenous shunt or vascularized lymph node transfer at the time of axillary dissection as another opportunity to prevent or reduce lymphedema severity. 38,39 Improving provider awareness of the substantial health care burden of lymphedema is quickly becoming a priority today, as evidenced by the passing of a federal bill specifically targeting lymphedema in January 2014. 40,41 The Lymphedema Diagnosis and Treatment Cost Saving Act expands insurance coverage for conservative lymphedema treatment in light of evidence suggesting the benefits of halting lymphedema disease progression.…”
Section: Risk Factors For Lymphedemamentioning
confidence: 99%
“…37 Others have advocated for prophylactic lymphovenous shunt or vascularized lymph node transfer at the time of axillary dissection as another opportunity to prevent or reduce lymphedema severity. 38,39 Improving provider awareness of the substantial health care burden of lymphedema is quickly becoming a priority today, as evidenced by the passing of a federal bill specifically targeting lymphedema in January 2014. 40,41 The Lymphedema Diagnosis and Treatment Cost Saving Act expands insurance coverage for conservative lymphedema treatment in light of evidence suggesting the benefits of halting lymphedema disease progression.…”
Section: Risk Factors For Lymphedemamentioning
confidence: 99%
“…In a group of 14 patients with subclinical lower extremity lymphedema from resection of a variety of gynecologic cancers, LVA effectively prevented symptomatic lymphedema [9]. Moreover, LVA successfully prevented lymphedema in a group of 23 women who underwent axillary lymph node dissection for breast cancer treatment [10]. The reported complication profile for this procedure also favors its use, as was seen in the meta-analysis aforementioned, showing a 3.9% incidence of infection, 4.1% incidence of lymphorrhea, and 10% requiring a subsequent operation [7].…”
Section: Lvamentioning
confidence: 99%
“…In animal models, several groups have demonstrated that exogenous treatment with VEGF-C/D stimulates post-natal lymphangiogenesis to improve lymphedema (4-7). However, reports that link VEGF-C expression with tumor metastasis [8][9][10] make VEGF-based therapy risky in patients with a history of cancer.…”
Section: Journal Of Aesthetic and Reconstructive Surgery Issn 2472-1905mentioning
confidence: 99%
“…During lymph nodal dissection also one or two collateral branches of the axillary vein are prepared with a length suitable for reaching the lymphatic vessels. The microsurgical technique of lymphatic venous anastomosis has already been described (11). The vein was averagely 2 mm in diameter and lymphatics about half mm.…”
Section: Operating Techniquementioning
confidence: 99%